2018
DOI: 10.1016/j.pmedr.2018.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the social norms intervention The GOOD Life on norm perceptions, binge drinking and alcohol-related harms: A cluster-randomised controlled trial

Abstract: The study aimed to investigate if the school-based social norms intervention The GOOD Life was effective in reducing misperceptions, heavy alcohol use and alcohol-related harms among Danish pupils aged 13–17 years.In total 38 schools were included in a cluster-randomised controlled trial and allocated to either intervention (n = 641) or control group (n = 714) during 2015/2016. Both groups completed an online survey before the intervention and 3 months after baseline. The GOOD Life intervention provided normat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 44 publications
2
23
0
2
Order By: Relevance
“…This is in line with TPB theory suggesting that change in perceived norms is related to changes in intention for a behaviour [3]. The effect evaluation of the trial also showed that overestimation of binge drinking among peers was significantly lower in the group receiving the The GOOD Life than in the control group [10]. Our finding that The GOOD Life motivated pupils to re-evaluate their own drug use behaviour is also supported by other research.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in line with TPB theory suggesting that change in perceived norms is related to changes in intention for a behaviour [3]. The effect evaluation of the trial also showed that overestimation of binge drinking among peers was significantly lower in the group receiving the The GOOD Life than in the control group [10]. Our finding that The GOOD Life motivated pupils to re-evaluate their own drug use behaviour is also supported by other research.…”
Section: Discussionsupporting
confidence: 90%
“…The study found that pupils' exaggerated perceptions regarding their peers' use and approval of alcohol use were related to personal experience with alcohol [9]. It also showed that receiving the intervention had a positive effect on norm perceptions and alcohol-related harms, but a preventive effect on binge drinking was only found among pupils with an intention to drink more alcohol [10]. Hence, SNA could be a suitable preventive strategy for alcohol prevention among Danish adolescents.…”
Section: Introductionmentioning
confidence: 88%
“…Cuijpers (6) suggest that the inconclusive results on effectiveness may be related to the inconsistency of programme content and the diversity of the theoretical frameworks of successful programmes. However, prevention programmes based on the social norms approach (SNA) have shown promising results in relation to reduction of alcohol use in educational settings among both younger (710) and older adolescents (11, 12). These SNA interventions place the focus on the healthy behavior of the majority of the target population, hence fosters social cohesion and inclusion rather than pinpointing toward adverse, or anti-social behavior.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, it is possible that those who defecate in the open overestimate the prevalence of this behavior to justify their behavior. On the other hand, it is also possible that this bias encourages individuals to adjust their behavior to coincide with their subjective prevalence perception [22]. As reported in Bicchieri, et al, 2018, toilet use was strongly influenced by the belief that other members of one's reference network are using toilets [19].…”
Section: Plos Onementioning
confidence: 99%